Effect of androgen deprivation therapy on the contractile properties of type I and type II skeletal muscle fibres in men with non‐metastatic prostate cancer. (28th November 2017) - Lamboley, Cedric R; Xu, Hongyang; Dutka, Travis L; Hanson, Erik D; Hayes, Alan; Violet, John A; Murphy, Robyn M; Lamb, Graham D
Summary: The contractile properties of vastus lateralis muscle fibres were examined in prostate cancer (PrCa) patients undergoing androgen deprivation therapy (ADT) and in age‐ and activity‐matched healthy male subjects (Control). Mechanically‐skinned muscle fibres were exposed to a sequence of heavily Ca 2+ ‐buffered solutions at progressively higher free [Ca 2+ ] to determine their force‐Ca 2+ relationship. Ca 2+ ‐sensitivity was decreased in both type I and type II muscle fibres of ADT subjects relative to Controls (by −0.05 and −0.04 pCa units, respectively, P  < .02), and specific force was around 13% lower in type I fibres of ADT subjects than in Controls ( P  = .02), whereas there was no significant difference in type II fibres. Treatment with the reducing agent dithiothreitol slightly increased specific force in type I and type II fibres of ADT subjects (by ~2%‐3%, P  < .05) but not in Controls. Pure type IIx fibres were found frequently in muscle from ADT subjects but not in Controls, and the overall percentage of myosin heavy chain IIx in muscle samples was 2.5 times higher in ADT subjects ( P  < .01). The findings suggest that testosterone suppression can negatively impact the contractile properties by (i) reducing Ca 2+ ‐sensitivity in both type I and type II fibres and (ii) reducing maximum specific force in type I fibres.